Addressing the high prevalence of gonorrhoea and chlamydia among female sex workers in Indonesia: results of an enhanced, comprehensive intervention. (15th February 2010) - Bollen, Liesbeth J M; Anartati, Atiek Sulistyarni; Morineau, Guy; Sulami, Siti; Prabawanti, Ciptasari; Silfanus, Fonny J; Esti, Prima Kartika; Nurhayati,; Mahatmi, Tiara; Sutarman, Leo; Rahadi, Wahyu; Natpratan, Chawalit; et al.
Abstract : Objectives: The authors developed a comprehensive STI-control programme to decrease gonorrhoea and chlamydia prevalence, and increase consistent condom use among brothel-based sex workers in Indonesia. Methods: The STI-control programme for brothel-based sex workers in Bintan Island (Riau Islands) and Salatiga (Central Java) included (1) provision of adequate drugs for gonorrhoea and chlamydia as periodic presumptive treatment (PPT) followed by syndromic treatment; (2) condom-use promotion by involving the local community and ensuring sufficient condom supply. Endocervical samples were collected and tested for gonorrhoea and chlamydia by PCR. Cross-sectional assessments of gonorrhoea and chlamydia prevalence, and consistent condom use with clients in the last week were made at several time points for sex workers attending the STI clinic. Results: 580 sex workers participated in the programme. A steady decrease in prevalence was observed for gonorrhoea (36.1–7.6%) and chlamydia (33.7–10.2%) (both p<0.01) among sex workers in Bintan from March 2008 until June 2009. Sex workers in Salatiga showed a sharp initial decrease in prevalence, followed by an increase after provision of the old drug regimen. Gonorrhoea and/or chlamydia prevalence among those who had received at least one PPT round was lower compared with that in newcomers (p<0.01). The proportion of sex workers reporting consistent condom use doubled to 40% in June 2009 compared with November 2007 (p<0.01). Conclusion: The STI-control programme was effective in reducing infection prevalence and increasing condom use among sex workers. This intervention has been scaled up and may decrease national STI levels and reduce HIV transmission.